PENGARUH KOMPETENSI AKUNTANSI TERHADAP KETERAMPILAN BERPIKIR KRITIS MAHASISWA (Studi korelasional pada mahasiswa Program studi Pendidikan Ekonomi di beberapa LPTK di provinsi Lampung) - Pujiati, Pujiati (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2015)
Effect Of Accounting Competencies Critical Thinking Skills To Students (Correlational study on Economic Education Study Program students in some LPTK in Lampung province). This research aims to study, measure, and analyze the effect of academic competence on students' critical thinking skills. The approach used is quantitative descriptive correlational analysis. The research sample includes respondents as many as 315 students of Economic Education from three LPTKs, that is, the University of Lampung of teacher training and education faculty, Teacher training and education faculty, University of Muhammadiyah Metro, and STKIP PGRI Bandar Lampung. The conclusion of this study is the effect on the competence of accounting students' critical thinking skills. The implications of the findings that critical thinking skills can be improved by accounting competence.